2018
DOI: 10.1021/acs.jpca.8b01384
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Preference Determined by C–H···π Interaction of an O–H···O Hydrogen-Bonded Binary Complex of p-Fluorophenol with 2,5-Dihydrofuran: A Laser-Induced Fluorescence Spectroscopy Study

Abstract: Conformational preferences of a binary hydrogen-bonded complex between p-fluorophenol (pFP) and 2,5-dihydrofuran (DHF) have been studied by means of laser induced fluorescence (LIF) spectroscopy in a supersonic jet expansion. Calculation predicts two major conformers for this complex, one having a nearly linear geometry in which the two molecular moieties are bound only by an O-H···O H-bond, but in the other an additional C-H···π type interaction between an ortho C-H group of pFP and ethylene group of DHF cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Additionally, the O-HÁ Á ÁO hydrogen bond, which is a classical strong interaction, exists widely in the crystal structures of carboxylic acids (Mukhopadhyay et al, 2018). From an analysis of the related hydrogen bonds herein, it is found that O-HÁ Á ÁO À hydrogen bonds [2.822 (3)-2.840 (3) Å ] involving water molecules of 1 are weaker than similar hydrogen bonds in 2.…”
Section: Discussion [Provide a More Descriptive Title?]mentioning
confidence: 93%
“…Additionally, the O-HÁ Á ÁO hydrogen bond, which is a classical strong interaction, exists widely in the crystal structures of carboxylic acids (Mukhopadhyay et al, 2018). From an analysis of the related hydrogen bonds herein, it is found that O-HÁ Á ÁO À hydrogen bonds [2.822 (3)-2.840 (3) Å ] involving water molecules of 1 are weaker than similar hydrogen bonds in 2.…”
Section: Discussion [Provide a More Descriptive Title?]mentioning
confidence: 93%
“…The O–H···π hydrogen bond, and its analogues N–H···π and C–H···π, have been reported as weak interactions that induce to some stabilization and have implications in the folding of biomolecules . However, they are not usually as strong as conventional hydrogen bonds, which is in stark contrast to our findings on Complex-1, wherein the O–H···π hydrogen bond stabilizes the complex to a larger extent.…”
Section: Resultsmentioning
confidence: 99%
“…4 The standard free energy barriers of the HO2-catalyzed and non-catalyzed tautomerisms are 17.9 and 53.64 kcal mol -1 , respectively. interactions that induce to some stabilization [35][36][37] and have implications in the folding of biomolecules. 36 However, they are not usually as strong as conventional hydrogen bonds, which is in stark contrast to our With the factors − ( ) , the rate constants for the forward and reverse reactions i-C3H5OH + HO2…”
Section: Numerical Simulations Of the Combustion Of S-c4h9ohmentioning
confidence: 99%
“…Understanding the physical origins of noncovalent interactions is an important task for EDA methods. GKS‐EDA and LMO‐EDA have been used to analyze various noncovalent interactions, including hydrogen bond, halogen bond, chalcogen bond, tetrel bond, pnicogen bond, π‐π stacking, cation⋯π, anion⋯π, XH⋯π (X = C, N, or O), and cooperative effects . Here we illustrate several representative applications for hydrogen bonds, halogen bonds and π‐π stacking, which show the diversity of physical origins in various noncovalent interactions.…”
Section: Applicationsmentioning
confidence: 99%